2008
DOI: 10.1002/anie.200803157
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Metal Catalysts for Intermolecular Carbenoid Insertion into Primary CH Bonds and Enantioselective CC Bond Formation

Abstract: Direct functionalization of CÀH bonds is an appealing strategy in organic synthesis [1] but its practical application has so far been difficult to realize. The selective functionalization of primary C À H bonds of alkanes that also contain secondary and/or tertiary C À H bonds is a great challenge, as CÀH bond energy follows an order primary > secondary > tertiary. [1c,d] In seminal works by Bergman, [1b] Jones, [1c] and their respective co-workers, stoichiometric reactions of alkanes with [Cp*(Me 3 P)M] (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 39 publications
1
67
0
Order By: Relevance
“…19,20 In this sense, porphyrin-based MOFs are reporting great results, [21][22][23] since Suslick et al reported the first catalytic activity of a porphyrinic coordination polymer with open structure. 24 In the last years, porphyrinic complexes of iron, 25 cobalt, 26 ruthenium, 27 rhodium, 28 among others, are known in literature to catalyze chemical reactions like, for example, olefin cyclopropanation and X-H (X = C, N, Si) bond insertion with high efficiency and selectivity. For instance, Rh-porphyrin complexes provide cyclopropanation and C-H primary insertion products with extraordinary selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 In this sense, porphyrin-based MOFs are reporting great results, [21][22][23] since Suslick et al reported the first catalytic activity of a porphyrinic coordination polymer with open structure. 24 In the last years, porphyrinic complexes of iron, 25 cobalt, 26 ruthenium, 27 rhodium, 28 among others, are known in literature to catalyze chemical reactions like, for example, olefin cyclopropanation and X-H (X = C, N, Si) bond insertion with high efficiency and selectivity. For instance, Rh-porphyrin complexes provide cyclopropanation and C-H primary insertion products with extraordinary selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Rh-porphyrin complexes provide cyclopropanation and C-H primary insertion products with extraordinary selectivity. 28 Further, Feand Ru-porphyrins can furnish the N-H insertion of ammonia 25 and peptides containing an N-terminal amine, 27 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Scheme 6.17, ca 90 % ee were achieved with cyclohexane (secondary C-H) and adamantane (tertiary C-H), whereas only 60 % ee was reached with 2-methylbutane. Ten years later, a rhodium- porphyrin catalyst [70] (II, Scheme 6.16) was described to give similar degrees of enantioselection, as well as the already mentioned high regioselection toward primary sites. Thus, hexane or 2,2-dimethylbutane were preferentially functionalized in the primary sites with the subsequent generation of the stereocenter.…”
Section: The Asymmetric Versionmentioning
confidence: 91%
“…As expected from the reactivity order, the primary benzylic position of toluene was completely inactive to insertion, in contrast with Rh catalysts. 20,24,25 …”
Section: Reactions Of Cumene and Ethylbenzene With Phenyldiazoacetatementioning
confidence: 99%